The UK Justice and Security Bill 2012–2013: Using secrecy to legitimize the securitization of the law - Pope, Mark (Media, War & Conflict, 2019)
The Justice and Security Act of 2013 provides for closed hearings in civil cases involving security sensitive information. The author argues that the UK Government successfully created and reinforced the authority of secretive sources to ensure the Bill was passed. Such authoritative sources promoted imaginaries of a future attack but also the need to respect legal principles that protected members of ‘our’ community. The dynamics between these imaginaries and principles led to the passing of the Bill in its final form – approving closed procedures in court, but removing inquests and issues of the ‘public interest’ from the Bill. Moreover, deliberation of the Bill was represented as negotiated and rational, thereby providing the final Act with legitimacy in elite fields. This research outlines how secrecy may not only be an end-goal of securitization moves, but reference to secret intelligence can also be integral to the justification of these moves.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xNzUwNjM1MjE3NzIxMTM1